Determining factors in the purchase intention of technological products in the city of Machala - Yaguana Márquez, Jhonny; Aguilar Gálvez, William (mktDESCUBRE; Vol 1 No 22 (2023): Twenty-second Edition (July - December), 2023)
At present, the purchase of technologies has achieved considerable, since they are having a significant impact on social life, however, there are aspects that affect the purchases of these technologies. Based on this, the objective of the study was to determine the factors that influence the intention to purchase technologies in the city of Machala. For this, it became a quantitative method, of a correlational type and the PLS-SEM methodology was developed, to carry out a multivariate analysis and verify through statistics the relationships of the established structural model. An online survey elaborated by 30 items was applied to 228 people through the Google form. The results showed that both the perceived quality, as well as trust, image and brand loyalty, have a positive and significant influence on the purchase intention. This allowed us to conclude that consumers in the city of Machala considering these factors as relevant in their lives when they seek to acquire a technological product.